Müller cells and retinal angiogenesis: critical regulators in health and disease - Medina-Arellano, Alan E.; Albert-Garay, Jesús Silvestre; Medina-Sánchez, Tania; Fonseca, Karla Hernández; Ruiz-Cruz, Matilde; Ochoa-de la Paz, Lenin (Frontiers in Cellular Neuroscience, 2024)
Müller cells are the most abundant glial cells in the mammalian retina. Their morphology and metabolism enable them to be in close contact and interact biochemically and physically with almost all retinal cell types, including neurons, pericytes, endothelial cells, and other glial cells, influencing their physiology by releasing bioactive molecules. Studies indicate that Müller glial cells are the primary source of angiogenic growth factor secretion in the neuroretina. Because of this, over the past decade, it has been postulated that Müller glial cells play a significant role in maintaining retinal vascular homeostasis, with potential implications in vasoproliferative retinopathies. This review aims to summarize the current understanding of the mechanisms by which Müller glial cells influence retinal angiogenesis in health and disease, with a particular emphasis on three of the retinopathies with the most significant impact on visual health worldwide: diabetic retinopathy, retinopathy of prematurity, and age-related macular degeneration.